Application of experimental designs in clinical trials: some particular cases with medications in Cuba - Javier Cruz Rodríguez; María Margarita Ríos Cabrera (Medisur)
Experimentation is a routine activity of utmost importance in the particular sciences that has contributed to the development of humanity and with high significance, especially in clinical trials. The purpose of this article is to exemplify, through different clinical researches with medications carried out in Cuba, how these studies are diagrammed, for their better understanding and execution.